The Authority of the Constitutional Court in Establishing New Norm Post-Amendment of the Indonesian Constitution - Timomor, Adensi; Lembong, Patrisia; Pangalila, Theodorus (Universitas of Muhammadiyah Makassar, 2024)
The problem in this research is that after the amendment of the Indonesian Constitution, the establishment of the Constitutional Court included judicial review as one of its authorities. As a court, the Constitutional Court generally acts as a negative legislator, where any law declared unconstitutional is declared null and void and not binding in any legal capacity. However, the Constitutional Court often formulates new norms to replace the unconstitutional provisions of the law, which leads to its position as a positive legislator. Therefore, the purpose of this research is to identify and analyze the basis and reasoning of the Constitutional Court in formulating new norms. In conducting this research, normative legal research method is used. The results show that the Constitutional Court creates new norms when there is a legal vacuum, the formulation of conflicting laws, or the emergence of various interpretations due to unclear or biased laws